KARAKTERISTIK TEKSTUR ROTI MANIS DARI TEPUNG, PATI, SERAT DAN PIGMEN ANTOSIANIN UBI JALAR UNGU - Jasmine Aldrina Iswara; Elisa Julianti; Mimi Nurminah (Jurusan Teknologi Hasil Pertanian, Fakultas Teknologi Pertanian, Universitas Brawijaya, 2019)
The aim of this research was to determine the effect of flour, starch, fiber, and anthocyanin pigment of purple sweet potato on characterization texture of sweet bread. This research was conducting using non factorial completely randomized design with one factor of 2 controls and 6 treatment of flour comparison : starch : fiber : anthocyanin pigment of purple sweet potato. The results of the analysis of the characterization texture of sweet bread showed that the comparison of flour, starch, fiber, and anthocyanin pigment of purple sweet potato had significant effect (P<0.05) on the texture (cohesiveness) and high significant effect (P<0.01) on texture (chewiness, adhesiveness, % deformation, hardness, gumminess, and springiness). Adding more purple sweet potato to sweet bread can increase cohesiveness, adhesiveness, springiness, and gumminess and decrease %deformation. While the addition of purple sweet potato fiber which is more and more on sweet bread can increase chewiness, hardness, and gumminess.